85 Cardiac resynchronisation therapy acutely alters metabolic substrate uptake, correlating with improvements in systolic function and long term reverse remodelling. (6th June 2022) - Green, Peregrine; Watson, William; De Maria, Giovanni Luigi; Lewis, Andrew; Rider, Oliver; Herring, Neil
Abstract : Introduction: The failing heart is thought to be metabolically inflexible, and oxygen limited, shifting from free fatty acid (FFA) oxidation towards glucose metabolism. Whilst glucose metabolism is more oxygen efficient, fatty acid (FA) metabolism generates more adenosine triphosphate (ATP) per mole of substrate. Cardiac resynchronisation therapy (CRT) acutely improves cardiac haemodynamics in patients with severe heart failure and a left bundle branch block. However, whether CRT alters metabolic substrate usage and whether this correlates with functional improvement is unknown.ObjectivesTo assess acute cardiac work, efficiency, and metabolic substrate uptake in response to CRT and correlate this with reverse remodelling. Methods: Participants with non-ischaemic cardiomyopathy were started on an insulin/dextrose infusion prior to CRT implant. During implant, measurements of left ventricular (LV) contractility (using a pressure-volume loop catheter), coronary flow (using a Doppler guide wire) and paired arterio-venous blood samples (from the left main stem and coronary sinus) were obtained with and without CRT at rest and during stress, pacing at 65% of predicted maximum heart rate. All measurements were repeated on a FFA infusion. Participants had cardiac magnetic resonance imaging at 6 months, with biventricular pacing in MRI-safe mode, to assess reverse remodelling. Results: Twelve participants were recruited (7 male, median age 64 [IQR 60–71]). Measures of LV contractility (work and dP/dtmax) were significantly improved by CRT at rest and stress on both infusions, without an increase in myocardial oxygen demand, resulting in improvement in cardiac efficiency (insulin/dextrose at rest:+7.9%, p = 0.02; stress: +67%, p = 0.03; FFA at rest: +31%, p = 0.02; stress: +57%, p = 0.09). Metabolic flexibility was therefore retained. On insulin/dextrose, CRT at rest increased cardiac FFA uptake (Figure 1A), which positively correlated with improvement in LV ejection fraction (LVEF, Figure 1B). When FFA uptake was already increased during stress, CRT increased lactate uptake (p = 0.02). When FFA uptake was maximised on a FFA infusion, CRT increased ketone uptake both at rest and during stress, which positively correlated with improvement in cardiac work (R = 0.55, p = 0.04). At all points, the heart was a net lactate consumer rather than producer, implying that oxygen supply was not limited. Participants underwent significant reverse remodelling at 6 months with reduction in LV end-diastolic volume (LVEDV) and this correlated with acute changes in FFA (Figure 2A) and ketone uptake (Figure 2B) with CRT. Conclusion: CRT improves cardiac efficiency and reverses the metabolic phenotype of heart failure towards more physiological lipid-based metabolism. Acute increases in FFA and ketone uptake correlate with improvements in contractility and reverse remodelling at 6 months. Therapy targeting lipid metabolism may therefore be a useful strategy in the failing heart. Conflict of Interest: Nil